2015
DOI: 10.2337/dc15-1588
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes as a Risk Factor for Dementia in Women Compared With Men: A Pooled Analysis of 2.3 Million People Comprising More Than 100,000 Cases of Dementia

Abstract: OBJECTIVEType 2 diabetes confers a greater excess risk of cardiovascular disease in women than in men. Diabetes is also a risk factor for dementia, but whether the association is similar in women and men remains unknown. We performed a meta-analysis of unpublished data to estimate the sex-specific relationship between women and men with diabetes with incident dementia.RESEARCH DESIGN AND METHODSA systematic search identified studies published prior to November 2014 that had reported on the prospective associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
386
7
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 532 publications
(425 citation statements)
references
References 27 publications
25
386
7
7
Order By: Relevance
“…We also observed sex differences in levels of HOMA-IR and HOMA-B between diagnostic groups, where upon stratification by sex, the increases observed in the MCI or AD groups were only observed in females. These findings are consistent with outcomes from meta-analyses which indicate women with T2D are at higher risk of stroke and dementia compared to men with T2D [19][20][21] and may be a consequence of several factors. For example, studies in different ethnic groups have suggested that age related increases in the prevalence of metabolic syndrome are greater in women then in men (see review ref.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also observed sex differences in levels of HOMA-IR and HOMA-B between diagnostic groups, where upon stratification by sex, the increases observed in the MCI or AD groups were only observed in females. These findings are consistent with outcomes from meta-analyses which indicate women with T2D are at higher risk of stroke and dementia compared to men with T2D [19][20][21] and may be a consequence of several factors. For example, studies in different ethnic groups have suggested that age related increases in the prevalence of metabolic syndrome are greater in women then in men (see review ref.…”
Section: Discussionsupporting
confidence: 88%
“…age, clinical staging of disease and disease progression) and study design. Further, recent meta-analyses suggest that sex can also mediate T2D associations with dementias and associated co-morbidities, such as stroke [19][20][21] . Thus, the relationship between IR and clinical and pathological features of the early stages of AD, and sex specific effects, requires further study, particularly in normoglycaemic individuals and prior to the onset of cognitive impairment.…”
Section: Growing Evidence Supports the Hypothesis That Type 2 Diabetementioning
confidence: 99%
“…Elderly people with diabetes have an especially increased risk of mild cognitive impairment (MCI) [18] and an association of diabetes with MCI varies with amyloid subtype (amnestic) MCI and nonamnestic MCI) and number of domains, and with the sex of the patient, with females being more susceptible than males [19]. Diabetes as a significant risk factor for dementia or AD has been clearly established by studies in the US [20] and several other countries (Taiwan [21], China [22], Japan [23], and Finland [24]). T2D has also been associated with an increased risk of vascular dementia [25], and pre-diabetic insulin resistance is a risk factor for AD pathology and reduced memory function [26].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Numerous studies have documented a strong association between diabetes and Alzheimer's Disease (AD) [16], [17], [18], [19], [20], [44]. However, the mechanisms underlying this association have not been clearly established.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Также показано быстрое развитие деменции у женщин с СД [67], что может частично объяснить психологические причины худшего контроля у них НУО. Arnetz L. с соавт.…”
Section: в Digami-2 доказано что уровень гпн в остром периоде им явлunclassified